The Circadian Clock, the Immune System, and Viral Infections: The Intricate Relationship Between Biological Time and Host-Virus Interaction - Gianluigi Mazzoccoli; Manlio Vinciguerra; Annalucia Carbone; Angela Relógio (Pathogens, 2020)
Living beings spend their lives and carry out their daily activities interacting with environmental situations that present space-time variations and that involve contact with other life forms, which may behave as commensals or as invaders and/or parasites. The characteristics of the environment, as well as the processes that support the maintenance of life and that characterize the execution of activities of daily life generally present periodic variations, which are mostly synchronized with the light−dark cycle determined by Earth’s rotation on its axis. These rhythms with 24-h periodicity, defined as circadian, influence events linked to the interaction between hosts and hosted microorganisms and can dramatically determine the outcome of this interplay. As for the various pathological conditions resulting from host−microorganism interactions, a particularly interesting scenario concerns infections by viruses. When a viral agent enters the body, it alters the biological processes of the infected cells in order to favour its replication and to spread to various tissues. Though our knowledge concerning the mutual influence between the biological clock and viruses is still limited, recent studies start to unravel interesting aspects of the clock−virus molecular interplay. Three different aspects of this interplay are addressed in this mini-review and include the circadian regulation of both innate and adaptive immune systems, the impact of the biological clock on viral infection itself, and finally the putative perturbations that the virus may confer to the clock leading to its deregulation.